BEYOND LIKES! INVESTIGATING THE INFLUENCE OF SOCIAL RELATIONSHIPS ON eWOM AND PURCHASE INTENTION IN SOCIAL MEDIA - Arora, Nilesh; Rana, Sudhir; Rana, Meghna; Prashar, Sanjeev; Tat, Huam Hon (Asian Academy of Management Journal, 2025)
The emergence and pervasive adoption of social networking sites (SNSs) have evolved the means in which people communicate and share information. Accompanying this advancement, electronic word-of-mouth (eWOM) has garnered considerable interest as a potent tool for information transmission and consumer decision-making. Given the interpersonal dynamics inherent in SNSs, this research investigates the association between antecedents of social relationship and eWOM as well as purchase intentions. Consequently, a conceptual model was constructed and validated to ascertain the significance of distinct factors, including interpersonal influence, social capital, homophily, and trust, as precursors to engagement in eWOM. The study also explored the moderating impact of social support on the association between eWOM intention and purchase intention. Additionally, the study analysed the moderating impact of gender on the relationship between interpersonal influence and eWOM intention. Using data from 383 respondents, the adequacy and accuracy of the model were assessed by employing partial least square technique of structural equation modeling (PLS-SEM). The results indicate that informative influence, bridging social capital, and trust have a favourable impact on users’ engagement in eWOM activities, which further effects purchase intention. On the other hand, normative influence, bonding social capital and perceived homophily demonstrated a negative relationship with eWOM engagement. These research findings have practical implications for marketers targeting new markets through eWOM activities.